A Description of Neonatal Death in the Perinatology Ward of Muhammadiyah Pekajangan Hospital, Pekalongan Regency - Yuliati, Y; Mustikawati, Neti (Prosiding University Research Colloquium, 2022)
Neonatal mortality reate is an indicator to determine the community health status involving various programs in the community. Neonatal mortality is defined as death in infants aged 0-28 days caused by maternal and infant factors. Objective: This study aims to describe neonatal mortality in the perinatalogy ward of Muhammadiyah Pekajangan Hospital Pekalongan Regency. Samples: A descriptive study with a longitudinal design was used. The research sample was neonates who died at 0-28 days in the perinatology ward of Muhammadiyah Pekajangan Hospital Pekalongan Regency in the 2017-2020 period as many as 57 documents. Methodes: The sampling technique used was total sampling. The research instrument used medical records. Data analyisis used univariate analysis with frequency distribution. Results: The results of the study showed that the majority of neonatal mortality was 66,7% male, 93,3% aged 0-6 days, 56,1% premature, 43,9% caesarean section and 61,4% low body weight. The cause of neonatal death is known to be 64,9% asphyxia. Conclusion: Recommendations for hospital are to analyze trend in the causes of neonatal deaths to be considered for hospital policy making in providing health services to pregnant and maternity women.